An empirical Study on Impact of Intellectual Human Capital on Corporate Social Innovation: Kajian Empiris Dampak Intellectual Human Capital terhadap Corporate Social Innovation - Alhasani , Abtihal Nasser; Alhinai , Marwa Hamed; Ahmed , Essia Ries (Journal of Accounting Science, 2023)
The study aims to explore the relationship between Intellectual Human Capital (IHC) and Corporate Social Innovation (CSI) in Oman. This research used a quantitative method. The population of this study was 74 companies on Muscat Stock Exchange (MSX) for the year ended 2021 in Oman. The sample size of this project was 63 from two sectors of listed companies (Financial Sector 31 and Industrial Sector 32). The study findings found there is a positive impact on the relationship between Intellectual Human Capital (IHC) and Corporate Social Innovation (CSI) in Oman. IHC contributes to increasing Social Innovation (SI) in companies, greatly influencing social innovation. Firms that use IHC have high social innovation because the IHC depends on the knowledge of human resources that impacts social innovation as it expands to other areas of the company.